Copper(II) and zinc(II) complexes bridged by benzenoid aromatic oxocarbon and dicarboxylate dianions. (1st April 2023) - Mautner, Franz A.; Fischer, Roland C.; Torvisco, Ana; Grant, Emeralde P.; Romain, Destiny S. St.; Salem, Nahed M.H.; Louka, Febee R.; Massoud, Salah S.
Graphical abstract: The interaction of Cu(ClO4 )2 and Zn(ClO4 )2 with croconate, C5 O5 2−, squarate, C4 O4 2− and pyridine-2, 5-dicarboxylate dianions in presence of tridentate or 4, 4′-bipyridine led to the production of novel series of penta-, tri- and di-nuclear metal complexes, whereas with 2, 2′-biphenyl dicarboxylate, a monomeric species was isolated. Abstract: A novel series of Cu(II) and Zn(II) complexes were constructed through the bridging croconate (C5 O5 ) 2−, squarate (C4 O4 ) 2− and 2, 5-pyridine-dicarboxylate (Py 2, 5-dc ) 2− dianions. These include pent- [Cu5 (epdmpy)4 (C5 O5 )2 (H2 O)6 ](ClO4 )6 ‧12H2 O (1 ) and tri-nuclear [Cu3 (bepza)2 (Py 2, 5-dc )2 (ClO4 )2 (H2 O)2 ]‧2H2 O (4 ), dinuclear [Zn2 (MeDPA)2 (C4 O4 )(H2 O)4 ](ClO4 )2 (7 ), and 1-D- coordination polymers (CPs) catena -{[Cu2 (bpzpy)2 (C5 O5 )](ClO4 )2 ‧MeOH} (2 ) and catena -{[Zn(4, 4′-bipy)(H2 O)4 ](C5 O5 )(H2 O)} (6 ) as well as the mononuclear [Cu(HBph 2, 2′-dc )(pmdien)]ClO4 (5 ) have been synthesized and spectroscopically characterized as well as by single crystal X-ray crystallography. The reaction of aqueous solution Cu(ClO4 )2, pymeea and C5 O5 2− resulted in the unprecedently bis(oxalato) [Cu2 (Pymeea)2 (C2 O4 )(ClO4 )2 (H2 O)2 ] (3 ). In these complexes, (C5 O5 ) 2−, squarate (C4 O4 ) 2− and (Py 2, 5-dc ) 2− ligands display a variety of coordination bonding modes. In complexes 1 and 2 the croconato is binding as 1, 2-bidentate-3-monodentate but in addition 5-mono-dentate semi-coordinate bonding was detected for 2, whereas in 6 as counter dianion. The bonding mode in the squarato 7 was achieved through the trans μ1, 3 -mono-dentate. In the di-carboxylato compounds, only five-membered chelate ring was formed in 5 via one of the carboxylate groups, whereas in 4 bridging was conducted through a mono-carboxylate and five-membered chelate ring including the second carboxylate and pyridyl nitrogen. In complexes 1 –5 and 7, hydrogen bonds of type OH⋯O and/or NH⋯O are connecting the complex cations with the perchlorate anions/ligands to generate different dimensional supramolecular network structures, whereas in 6, the 3D network was formed through hydrogen bonding between the coordinated aqua and lattice water molecules. Non-covalent ring⋯ring interactions were also observed between pyridyl rings in complexes 1, 6 and 7, and between pyrazolyl rings as well as pyridyl ring in 2 .